Uma imagem de Heródoto : a apropriação da historiografia herodoteana feita por Voltaire - Laís Pazzetti Machado (2022)
This study has the aim to investigate the construction of an image of the Greco-Roman antiquity as of the appropriation of Ancient historiography performed by Voltaire, within his project of history. From the perspective of the uses of the past, we will seek to understand which elements of the French scene in the XVIIIth century influenced Voltaire’s view of the Antiquity, how the knowledge concerning Ancient times was built (which were the sources available at the time, whether there was a direct access to the works of Ancient historians, or if the recourse to translations was predominant), which sources were used by Voltaire and what the image built by the philosopher can reveal about his interests. We will turn our attention to the rationalizing perspective of Voltaire’s philosophy of history, and to how, in its scope, Ancient historiography serves to different purposes, from the association with the idea of “falseness” included in the notion of “fable” to lessons that can be learned from Ancient historians, revealing that Voltaire engages in more complex uses of Ancient historiography – and of Antiquity herself – than what could be assumed at first. More specifically, we will focus on the lexicon of historical certainty created by Voltaire for his historiographical work and on the lexicon of historical certainty created by Herodotus, the Ancient author that Voltaire targets the most, so that we may be able to analyse the uses that the philosopher makes of the Greek historian.